Detection Biases in Bluffing - Håkan J. Holm (Lund University, School of Economics and Management, Department of Economics, 2008)
Beliefs in signals that reveal lies or truths are widespread. These signals may lead to a truth or lie detection bias if the probability that such a signal is perceived by the receiver is contingent on the truth value of the sender's message. Such detection biases are analyzed theoretically in a bluffing game. The detection bias shrinks the equilibrium set to a unique non-pooling equilibrium, in which the better a player is at detecting lies the more often the opponent player will lie. With proper deception techniques such biases can in principle be used to extract hidden information.
Keywords: C72; D82; 330; Bluffing; Game theory; Truth detection; Lie detection; Detection bias